From a Railway Junction to a Corridor - Évora’s railway history through Iberian Railway Connections - Lourencetti, Fernanda de Lima (História: revista da Faculdade de Letras da Universidade do Porto, 2026)
As a contribution to expand and promote knowledge about Évora’s railway heritage, at a time of modernization and cultural appreciation, this article chronicles the Évora railway junction, and presents the new railway corridor built between Sines and Madrid, to describe the current situation of the first railway infrastructure. Considering that, in parallel with the construction of the new railway line, the city is in preparation to become European Capital of Culture in 2027, this article concludes that Évora's railway history is relevant in the context of Iberian railway connections as a complement to historical transport studies of the city.